'Which journal is that?' Politics of academic promotion in Uganda and the predicament of African publication outlets. Issue 3 (1st September 2020) - Ssentongo, Jimmy Spire
Abstract : Research and publication are some of the practices that define university work and therefore are part and parcel of the key considerations for promoting university-based academics. Whereas this promotion standard is widely appreciated in view of the importance of knowledge production, it raises several questions about the subtexts of its practice and their implications for publication in Africa. Through an empirical qualitative study of two Ugandan universities, this paper examines how promotion policies shape publication outlet choices and Africa-based publication initiatives. I show that promotion processes in Ugandan universities are driven by complex quality checks that are sometimes characterized by rationalized malice against individual academics in settling personal scores and biases against publications from African outlets. With the partial aid of theories of (post)coloniality and Southern theory, I explain the root of Afro-pessimistic biases in promotion criteria and argue that both the genuine quality checks and other neo-colonial biases incentivise publishing in the West and lead scholars to avoid African options. This exacerbates the already challenging circumstances of African publishers, limits local access to marketplaces of knowledge, and shrinks space for epistemic pluralism.